Impact of economic conditions on (restricted) immigration to the United States: The Polish case - Michał Schwabe (International Journal of Management and Economics, 2021)
Throughout the twentieth century, United States has been the most desirable destination for international migrants, primarily due to its economic performance and also to American values - work ethics and tolerance of ethnic diversity. This paper aims to test if selected economic indicators might influence international migration. To this end a time series analysis was performed with time series regression model, where lagged values of various macroeconomic indicators were tested for a significant impact on migration flows. This paper also cast a light on U.S. labour migration's legislation and history, as well as current migrant stock characteristics. It gives specific attention to Polish migrant population, as Polish Americans constitute the largest Polish diaspora worldwide. The results of the analysis show that U.S. immigration volumes are sensitive to American unemployment rate and American GDP growth (pull factors). However, analysing Polish migration volumes to the U.S. a significant correlation with selected American indicators was not revealed. On the contrary, Polish migration flows to the U.S. were correlated with Polish economic growth and the Polish unemployment rate fluctuations (push factors).
Keywords: F22; K37; J61; 650; Polish migration to the United States; immigration to the United States; impact of business cycle on labour migration; international labour migration; United States immigration law